Frequency of gestational diabetes mellitus using DIPSI criteria, a study from Pakistan - Musarrat Riaz; Asmat Nawaz; Shabeen Naz Masood; Asher Fawwad; Abdul Basit; A. Samad Shera (2018)
BackgroundGestational diabetes mellitus [GDM] is associated with adverse maternal and fetal outcome. It is a severe threat to maternal and child health in a resource constraint country like Pakistan.ObjectiveTo find out the frequency of GDM in two metropolitan cities of Pakistan using DIPSI criteria.MethodologyThis cross sectional study was conducted between 2013–2016 in various primary, secondary and tertiary care hospitals of two metropolitan cities namely Karachi and Hyderabad in Pakistan. All pregnant women attending the ante natal clinics of recruitment sites during this period were included in the study. After taking consent patients were given 75 g of glucose dissolved in 100 ml of water in non-fasting state using Diabetes in pregnancy Study group of India(DIPSI) criteria. Blood samples were collected after two hours.ResultsA total of 11,430 participants were included in the study. Mean gestational age was 27.12 ± 6.84 weeks with 18.8% and 23.1% having positive family history of diabetes and hypertension respectively. Previous history of GDM was present in only 6.8% of participants. About 1349(11.8%) pregnant women were diagnosed with gestational diabetes out of which 6.2%, 39.9% and 51.1% were diagnosed in 1st 2nd and 3rd trimester respectively. No known risk factor regarding GDM was present in 25.6% women.ConclusionThis study shows a high frequency of GDM (11.8%) irrespective of risk factors, and in all trimesters of pregnancy emphasizing the need for universal screening in Pakistan.